クリッギング補間を用いて推定した南極大陸の気温分布図(2) - 佐々木, 順一; SASAKI, Junichi; ササキ, ジュンイチ; 畑中, 雅彦; HATANAKA, Masahiko; ハタナカ, マサヒコ; 板倉, 賢一; ITAKURA, Ken-ichi; イタクラ, ケンイチ; 和田, 誠; WADA, Makoto; ワダ, マコト; et al. (室蘭工業大学, 1999)
application/pdf An atmospheric temperature map in the Antarctica is obtained by using krigging interpolation method based on Geostatistics. To create this temperature map, observed temperature data and location data at 209 stations in Antarctica are used. We have obtained those maps in every month until now. In this paper, we investigate the variation rate of temperature (both interpolated temperature and distributed one) and correlation coefficient between temperature and height above the sea level. 投稿論文 departmental bulletin paper